Аналіз технологій отримання кольорових естампних відбитків за допомогою глибокого друку - Дрімайло, М. М.; Хамула, О. Г. (Київ: ТОВ «Видавництво Ліра-К», 2025)
The technology of producing color printmaking intaglio prints was analyzed. The main printing technologies were considered and the priority method was selected. The technology of printing color intaglio prints, the specifics of materials and the specifics of printing are highlighted. The study provides an understanding of what exactly affects the quality and specifics of using this printing technology.
Keywords: глибокий друк; естампні відбитки